Sociodemographic determinants and regional disparities of first-trimester antenatal care initiation among Nigerian women: a multilevel analysis of 2018 NDHS data - Tadese, Zinabu Bekele; Sani, Jamilu; Kebede, Shimels Derso; Kitil, Gemeda Wakgari; Dube, Geleta Nenko; Nimani, Teshome Demis (Frontiers in Global Women's Health, 2025)
BackgroundMaternal health remains a critical public health priority, particularly in low- and middle-income countries where maternal mortality rates are alarmingly high. Early antenatal care (ANC) initiation within the first trimester is essential for identifying and managing potential health risks for both mothers and their babies. Despite global efforts to promote early ANC, significant disparities persist, especially in Nigeria. This study investigates the sociodemographic determinants and regional disparities influencing the timing of ANC initiation among Nigerian women.MethodsThis study utilized data from the 2018 Nigeria Demographic and Health Survey (NDHS), analyzing a sample of 16,542 women aged 15–49 who had given birth within five years of the survey. A multivariable multilevel logistic regression model was employed to assess the impact of individual and community-level factors on early ANC initiation. The model accounted for regional clustering to identify the most significant predictors of first-trimester ANC contact.ResultsThe analysis revealed that only 24.0% (n = 3,970) of Nigerian women-initiated ANC in the first trimester, with substantial regional disparities. The South West region had the highest prevalence (34.5%, n = 1,045), while the North West region had the lowest (12.5%, n = 609). Multivariable analysis showed that women with higher education were nearly twice as likely to initiate ANC early (AOR = 1.98, 95% CI: 1.65–2.37). Muslim women had lower odds of early ANC initiation than Catholics (AOR = 0.64, 95% CI: 0.47–0.87). Wealthier women had a significantly higher likelihood of early ANC, with the richest women being nearly three times more likely than the poorest (AOR = 2.88, 95% CI: 2.49–3.33). The final multilevel model showed a reduced intraclass correlation coefficient (ICC) of 2.6%, indicating that regional variation in ANC initiation.ConclusionThe findings highlight significant sociodemographic and regional disparities in the timing of ANC initiation among Nigerian women. To improve early ANC uptake, targeted interventions that address both individual barriers, such as education and economic status, and broader regional disparities are essential.